Transformações organizacionais e gestão de pessoas no setor financeiro - Silva, Otavio Tosi da (2012)
This research aims at studying the impact on the human resources processes used in banks in Brazil that have participated in the process of merger and acquisition. There was also a specific purpose to conduct a review of the literature on organizational transformations and personnel management in the financial sector. This study approaches comparative multiple case study in two organizations, through qualitative research. The banks Santander and Banco do Brasil were selected as research subjects. Data were collected through semi-structured exploratory interviews, besides analysis of documents and sites. The survey showed that in both banks the human resources policies are well developed, but the practical implementation is still weak. The main focus is to achieve the established targets, no matter in what form. Thus, the best human resources practices are eventually put aside. Another finding was that the relationship of financial institutions with the labor union, due to downsizing policy and changes from the automation processes, has been under transformation, which points to the need for changes in the practices of union institutions